RTS noise reduction of CMOS image sensors using amplifier-selection pixels - Mustafa, Mohd Amrallah; Seo, Min Woong; Kawahito, Shoji; Yasutomi, Keita; Kagawa, Kiichiro (The Institute of Electronics, Information and Communication Engineers, 2013)
This paper describes a RTS (random telegraph signal) noise reduction technique for an active pixel CMOS image sensor (CIS) with in-pixel selectable dual source-follower amplifiers. In this CMOS image sensor, the lower-noise transistor in each pixel is selected in the readout operation using a table of determining the lower-noise transistors of all the pixels. A prototype image sensor with 65×290 pixels for demonstrating the effectiveness of this technique has been implemented using 0.18µm CMOS image sensor technology with pinned photodiode option. The measured result shows that the maximum noise using the amplifier-selection technique is reduced to 9.6e- from 17.2e- which is the maximum noise of the image array using one of two amplifiers in each pixel without selection.